Pressure‐Induced Indirect‐Direct Bandgap Transition of CsPbBr3 Single Crystal and Its Effect on Photoluminescence Quantum Yield (Adv. Sci. 29/2022). Issue 29 (14th October 2022) - Gong, Junbo; Zhong, Hongxia; Gao, Chan; Peng, Jiali; Liu, Xinxing; Lin, Qianqian; Fang, Guojia; Yuan, Shengjun; Zhang, Zengming; Xiao, Xudong
Abstract : CsPbBr3 Single Crystal High pressure exerted on CsPbBr3 single crystal using diamond anvil cell leads to improved photoluminescence intensity due to the decreased dynamic Rashba splitting. Application of higher pressure transforms it into a pure indirect bandgap phase, which can be maintained at near‐ambient pressure. These phenomena provide a novel framework to understand the optoelectronic properties of perovskite materials. More details can be found in article number 2201554 by Junbo Gong, Zengming Zhang, Xudong Xiao, and co‐workers.